Uterine B Cells Exhibit Regulatory Properties During the Peri-Implantation Stage of Murine Pregnancy - Guzman-Genuino, Ruth Marian; Eldi, Preethi; Garcia-Valtanen, Pablo; Hayball, John D.; Diener, Kerrilyn R. (Frontiers in Immunology, 2019)
A successful outcome to pregnancy is dependent on the ability of the maternal uterine microenvironment to regulate inflammation processes and establish maternal tolerance. Recently, B cells have been shown to influence pregnancy outcomes as aberrations in their numbers and functions are associated with obstetric complications. In this study, we aimed to comprehensively examine the population frequency and phenotypic profile of B cells over the course of murine pregnancy. Our results demonstrated a significant expansion in B cells within the uterus during the peri-implantation period (day 2.5-8.5 post-coitus), accompanied by alterations in B cell phenotype. Functional evaluation of purified uterine B cells from pregnant mice at implantation (day 5.5 post-coitus) established their regulatory capacity as evidenced by effective suppression of proliferation and activation of syngeneic CD4+ T cells. Flow cytometry profiles revealed that the uterine B cell population has an expanded pool of IL-10-producing B cells bearing upregulated expression of co-stimulatory molecules CD80 and CD86 and activation marker CD27. Our investigations herein demonstrate that during the critical stages surrounding implantation, uterine B cells are amplified and phenotypically modified to act in a regulatory manner that potentially contributes towards the establishment of maternal immunological tolerance in early pregnancy.